Population biology of Astyanax lacustris (Pisces, Characiformes) in a Neotropical reservoir and its tributaries - Vidotto-magnoni, Ana P.; Kurchevski, Gregório; De Lima, Felipe P. [UNESP]; Nobile, André B. [UNESP]; Garcia, Diego A.z.; Casimiro, Armando C.r.; Pereira, Alan D.; Orsi, Mário L. (Academia Brasileira de Ciências, 2021)
The aging process of reservoirs has been extensively investigated; however, little is known about how fish populations are adjusted after many years of impoundment. Thus, this study aimed to compare the diet, length-weight relationship, sizes classes, variation in size, and age of Astyanax lacustris Lütken, 1875 collected from lotic and lentic habitats of an aging reservoir. The study group consisted of 730 captured fishes. We found that specimens collected from lotic habitats had a wider range of size classes (1.0 to 12.0 cm), were linked to a high frequency of juveniles (48.7%), and had greater feeding activity (higher stomach fullness). In contrast, fishes collected from lentic environments exhibited high rates of capture (78.4%), increased frequency of adults (87.3%), and higher values of mean standard length. The length-weight relationship indicated that lentic fishes were heavier than fish collected from lotic areas. Moreover, we observed 37 food items in A. lacustris diet, mainly plant material, algae, Cladocera, Hymenoptera, Coleoptera, and Ephemeroptera. Differences among the diet of fishes between sites were evidenced with Permanova (p < 0.05). Astyanax lacustris can be considered a persistent species in Chavantes Reservoir after aging, encountering conditions to complete its life span and adjusting to food resources.
Keywords: Characidae; native species; reservoir aging; upper Paraná River basin